International financial management - Bekaert, Geert (Cambridge University Press, 2018)
International Financial Management blends theory, data analysis, examples and practical case situations to equip students and business leaders with the analytical tools they need to make informed financial decisions and manage the risks that businesses face in today's competitive global environment.